INOVASI DESAIN PRODUK UMKM: APLIKASI SCAMPER DI KELAS STUDIO DESAIN PRODUK - Nurrul Haq, Bayyinah (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Collaboration between higher education institutions and industry in learning activities can strengthen their roles in enhancing industrial competitiveness, such as through partnerships between MSMEs in the creative sector and design programs for product innovation. Product design is a key factor in boosting product competitiveness. This study discusses implementing the SCAMPER technique as an idea development method in the Product Design Studio 4 course at Trilogy University. This course adopts a Project Based Learning approach involving MSMEs as partners, where students act as